PERAN ORANG TUA DALAM MENDIDIK ANAK MENURUT AMSAL 29:15, 17 - Nelly Nelly; Lidia Merlin Sweny (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
A child's success or achievement is influenced by various factorssupporting and inhibiting factors. One of the supporting factors is correct upbringing from parents, although this factor is not the only one, it has a big influence on a child's success. This article specifically aims to provide an understanding and application of the role of parents in educating children based on the book of Proverbs 29:15,17. In fact, parents have a very important role in educating a child's personality because parents are the most important educators for a child's life, especially in getting to know God, and developing the child's abilities and intelligence. By using the exegesis method, namely looking for the original meaning of the book of Proverbs 29:15.27, it can be concluded that the role of parents in educating children is to reprimand, not let it go, give advice, discipline and give warnings.